2023
DOI: 10.1002/anie.202216962
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Modified Poly(vinyl Alcohol)s and Their Degradation Using an Enzymatic Cascade

Abstract: Poly(vinyl alcohol) (PVA) is a water-soluble synthetic vinyl polymer with remarkable physical properties including thermostability and viscosity. Its biodegradability, however, is low even though a large amount of PVA is released into the environment. Established physical-chemical degradation methods for PVA have several disadvantages such as high price, low efficiency, and secondary pollution. Biodegradation of PVA by microorganisms is slow and frequently involves pyrroloquinoline quinone (PQQ)-dependent enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The methods for PA biodegradation are currently limited by low activity, however the fastgrowing bank of knowledge about engineering enzymes and microbes for other plastics can be utilized to find solutions to this problem. One example is the cascade of enzymes currently being explored for the depolymerization of another fossil fuel-derived plastic, polyvinyl alcohols (PVA) 78 .…”
Section: Polyurethanes (Pur)mentioning
confidence: 99%
“…The methods for PA biodegradation are currently limited by low activity, however the fastgrowing bank of knowledge about engineering enzymes and microbes for other plastics can be utilized to find solutions to this problem. One example is the cascade of enzymes currently being explored for the depolymerization of another fossil fuel-derived plastic, polyvinyl alcohols (PVA) 78 .…”
Section: Polyurethanes (Pur)mentioning
confidence: 99%
“…143 PVA is biodegradable under both aerobic and anaerobic conditions, 144 but the process may be slow, relying upon pyrroloquinoline quinone (PQQ) dependent enzymes and hence availability of this cofactor. 145 von Haugwitz et al 146 have reported a PQQ-independent enzymatic cascade reaction using commercially-available enzymes which can partially biodegrade PVA, presenting scope to incorporate the process into wastewater treatment.…”
Section: Strategies For the Design Of Biodegradable Polymersmentioning
confidence: 99%